Pendampingan Pembuatan LKPD berbasis digital dengan menggunakan Liveworksheet untuk para guru di MA Nurul Huda - Andriani, Dwi; Irawan, Indra; Afifah, Siti; Haidorizal, Rifkan (Journal Of Human And Education (JAHE), 2025)
MA Nurul Huda has utilized Teaching Aids in the learning process, but it is still in print form, despite the school facilities strongly supporting the use of digital Teaching Aids in the learning process due to the limited technological literacy of the teachers. Based on observations, it was also found that teachers only leave assignments and notes when the standby teacher is not present at school, resulting in an unconducive classroom atmosphere. Therefore, training and mentoring in the use of interactive Teaching Aids based on Liveworksheet are implemented to address these issues. With the method of introduction, training, practice, and mentoring, along with evaluation using Google Forms, it was found that 99% of the material delivery by the resource person is excellent, 85% of the service during the activity is good, 100% of the conveyed material is considered very important and beneficial by the participants, 84% find the practice of creating Liveworksheet media easy to understand, with difficulties mainly related to internet access. Furthermore, 80% of the mentoring activities via WhatsApp are intensive. This indicates that the activities are smoothly conducted and have a positive impact on the participants. It is expected that this will boost the enthusiasm of teachers in using technology for the progress of students